Healthcare personnel on the frontline of immunization: Barriers to vaccination and the path to full coverage - Saliha Büşra Aksu; Seda Özmen Sever; Beray Gelmez Taş; İlknur Demir; Güzin Zeren Öztürk (Human Vaccines & Immunotherapeutics)
This study assessed vaccination attitudes, behaviors, and influencing factors among 2,100 healthcare personnel (HCP) at Şişli Hamidiye Etfal Training and Research Hospital. Data were collected through structured interviews and analyzed using SPSS (Version 26.0). Although 86.4% of HCP acknowledged the importance of vaccines, only 72.6% had received at least one, and just 3.9% were completely vaccinated against hepatitis A, hepatitis B, tetanus, measles-mumps-rubella, and varicella. Full vaccination rates were higher among women, physicians, outpatient clinic staff, and alcohol users but declined with age and professional experience (p < .01). Barriers to influenza vaccination included fear of side effects (53.2%), perceived lack of necessity (21.2%), and insufficient information (11.0%). Physicians were 2.1 times more likely to be completely vaccinated than other HCP (OR: 2.148, p = .005). Despite strong vaccine awareness, immunization rates remain suboptimal. Targeted educatiunization rates remain suboptimal. Targeted educational efforts are essential to improve vaccine uptake and enhance HCP’s role in patient immunization advocacy.